Federal Deposit Insurance, Regulatory Policy, and Optimal Bank Capital* - BUSER, STEPHEN A.; CHEN, ANDREW H.; KANE, EDWARD J. (Journal of Finance, 1981)
ABSTRACT This paper seeks to explain the combination of explicit and implicit pricing for deposit insurance employed by the FDIC. Essentially, the FDIC sells two products—insurance and regulation. To span the product space, it must and does set two prices. We argue that the need to establish regulatory disincentives to bank risk‐taking is the heart of the controversy over the adequacy of bank capital and that the ability to close risky banks before exhausting their charter value (i.e., the value of their right to continue in business) stands at the center of these disincentives and in front of the FDIC's insurance reserves.